Characteristics of Bus Transit Vehicles in the United States: A 30-Year National Trend Analysis. Issue 8 (December 2018) - Tang, Li; Gan, Albert; Cevallos, Fabian; Alluri, Priyanka
In 2015, transit agencies in the United States spent over 60% of their bus transit capital funds on their revenue vehicles. Using 30 years of data from the National Transit Database (NTD), this paper examines the national trends of seven major characteristics associated specifically with bus revenue vehicles. These trends can provide important information on where the market might be heading and aid in planning decisions on transit investments. The characteristics examined include the number of vehicles, spare ratio, average age, average capacity, Americans with Disabilities Act (ADA) accessibility, vehicle reliability, and vehicle operations and maintenance expenses. Some findings from the trend data include: (1) a steady increase in the privatization of bus services; (2) the average spare ratios have consistently exceeded the maximum of 20%, as suggested by the Federal Transit Administration (FTA) for systems operating with more than 50 vehicles; (3) vehicles operated by contractors tended to be significantly newer than those operated directly by transit agencies, although the gap has narrowed in recent years; (4) vehicles operated directly by transit agencies tended to have higher seating and standing capacities than those operated by contractors; (5) there was a tendency among transit agencies to trade seats for more standing room; (6) by 2015, nearly all bus vehicles were ADA-compliant, and increasingly vehicles with lifts were converted to vehicles with ramps/low-floor; (7) reliability of vehicles considering the number of mechanical failures per million revenue vehicle miles has significantly improved over the years; and (8) contractors spent significantly less on average than transit agencies in operating and maintaining their vehicles.